Multidisciplinary management of early rectal cancer – The role of surgical local excision in current and future clinical practice. (March 2022) - Smits, Lisanne J.H.; van Lieshout, Annabel S.; Grüter, Alexander A.J.; Horsthuis, Karin; Tuynman, Jurriaan B.
Abstract: The implementation of bowel cancer screening programs has led to a rise in the incidence of early rectal cancer. The combination of increased incidence and the growing interest in organ-sparing treatment options has led to an amplified importance of local excision techniques in treatment strategies for early rectal cancer. In addition, developments in new technologies of single-port surgery have popularized surgical techniques. Although local treatment of early rectal cancer seems promising, a multidisciplinary approach is necessary and awareness of the oncological robustness is warranted to enable shared decision-making. This review illustrates the position of surgical local excision in the treatment of early rectal cancer and reflects on its role in current and future clinical practice. Highlights: Local excision as final therapy should depend on patient and tumour characteristics. Imaging is hampered by overstaging and may lead to overtreatment. Completion TME leads to good oncological outcomes, but is associated with morbidity. Local excision followed by chemoradiotherapy seems an attractive future perspective. A multidisciplinary approach contributes to patient tailored treatment.